Operational Budgeting Management - Dr. Bheem Sen Yadav (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2018)
The study is based on the importance of the method of operational budgeting. The impacts and significance of this method are critically evaluated in the entire study with the help of appropriate proof and examples. There are also mentioned several articles along with the suitable example of the method of operational budgeting. The methods and the findings of the entire study are very approachable for evaluating and understanding the significance of the fact properly by the readers as well as the management of several organizations.